Harnessing the Electrophilicity of Keteniminium Ions: A Simple and Straightforward Entry to Tetrahydropyridines and Piperidines from Ynamides. (2nd March 2016) - Lecomte, Morgan; Evano, Gwilherm
Abstract: An efficient, modular and straightforward entry to tetrahydropyridines and piperidines is reported. This reaction is based on a formal intramolecular hydroalkylation of readily available, properly substituted ynamides which, upon simple activation under acidic conditions, generate highly reactive activated keteniminium ions whose reactivity can be finely controlled to induce a remarkably efficient [1, 5]‐hydride shift from unactivated C−H bonds and trigger a cationic cyclization which is complete within minutes.